Prospective study of changes in the metabolomic profiles of men during their first three months of androgen deprivation therapy for prostate cancer - Saylor, Philip J. (2012)
BACKGROUND: Androgen deprivation therapy (ADT) for prostate cancer causes a rise in fasting insulin and adverse changes in body composition and serum lipid profile. It is unknown what other metabolic alterations are caused by ADT. In order to better characterize the metabolic effects of ADT, we measured changes in plasma metabolomic profile at baseline and after the first three months of therapy. METHODS: Fasting plasma samples were drawn from 36 subjects at baseline and after three months of gonadotropin releasing hormone (GnRH) agonist therapy. Extracted samples were split into equal parts for analysis on the gas chromatography/mass spectrometry and liquid chromatography/tandem mass spectrometry platforms. RESULTS: Of the 292 identified metabolites, 56 changed significantly (p<0.05) from baseline to three months. Notable changes were grouped as follows: (a) Multiple steroids were lower at three months, consistent with the effect of therapy on gonadal androgen synthesis. (b) Most bile acids and their metabolites were higher during treatment. Cholesterol levels changed very little. (c) Markers of lipid beta-oxidation (acetyl-carnitines, ketone bodies) and omega-oxidation were lower at three months. (d) Two previously-identified biomarkers of insulin resistance (2-hydroxybutyrate, branch chain keto-acid dehydrogenase complex products) were stable to lower at three months. CONCLUSIONS: Unbiased metabolomic analyses revealed expected, novel, and unexpected results. Steroid levels fell, consistent with the effects of ADT. Most bile acids and their metabolites increased during ADT, a novel finding. Biomarkers of lipid metabolism and insulin resistance fell, unexpected given that ADT has been shown to increase fasting insulin.